Mimesis and Archetype. Philo rescues the platonic Poet (Circe de clásicos y modernos, 2018)
This paper examines the topic of imitative poetry in Plato. Its aim is to determine whether, for Plato, may be a mimesis of value and consequently an acceptable mimetic poetry. For this, two sections concerning a valid Republic imitation will be analyzed. This would be based on the dialectical understanding of intelligible realities; condition that the poet can not be covered. My hypothesis is that the solution to this problem is the Platonic idea of ‘design’, which -derived the ideal paradigm- would be the tool for the imitator. Philo has conceptualized this tool in his idea of archetype.
Keywords: mimesis; paradigm; archetype; Plato; Philo